MODELING OF PLANT EMBRYO MORPHODYNAMICS AT EARLY DEVELOPMENTAL STAGES - S. V. Nikolaev; N. A. Kolchanov; S. K. Golushko; J.-C. Palauqui; A. Urban; E. V. Amelina; A. V. Yurchenko; K. S. Golushko; U. S. Zubairova; A. V. Penenko; A. Trubuil (Вавиловский журнал генетики и селекции)
Embryo morphodynamics at early developmental stages of Arabidopsis thaliana was studied. First, a pipeline was elaborated from confocal microscopy and tissue 3D reconstruction to cell lineage tree reconstruction and numerical simulation of growing embryo mechanics. Tentative results of its use are presented.